Comparison of Surgical Site Infection in Absorbable and Non-Absorbable Sutures Among Patients Undergoing Abdominal Wound Closure After Laparotomy: A Randomized Controlled Trial - Salam, Abdul; Akbar, Fazli (Biological and Clinical Sciences Research Journal, 2025)
Surgical site infection remains a common postoperative complication following laparotomy and is influenced by several operative factors, including the type of suture material used for abdominal wound closure. Objective: To compare the frequency of surgical site infection in absorbable and non-absorbable sutures in patients undergoing abdominal wound closure after laparotomy. Methodology: This study included 144 patients undergoing abdominal wound closure after laparotomy and were allocated into two equal groups using blocked randomisation. Group A underwent wound closure with an absorbable polydioxanone suture, while Group B received closure with a non-absorbable polypropylene suture. Surgical site infection (SSI) was assessed in both groups at 21 days post-procedure. Data was analyzed using SPSS 27. Results: The mean age of patients in Group A was 43.76 ± 15.44 years, while in Group B it was 46.53 ± 14.43 years. In both groups, males had a majority. A statistically significant difference in SSI incidence was observed. In the absorbable suture group, 16 patients (22.2%) developed an SSI. In the non-absorbable suture group, 30 patients (41.7%) developed an SSI (p=0.01). Conclusion: The frequency of surgical site infection was significantly higher in non-absorbable sutures in patients undergoing abdominal wound closure after laparotomy as compared to absorbable sutures.